2010
DOI: 10.1007/s10530-010-9924-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exotic Spartina alterniflora on the habitat patch associations of breeding saltmarsh birds at Chongming Dongtan in the Yangtze River estuary, China

Abstract: Smooth cordgrass (Spartina alterniflora)is one of the most invasive exotic plants of saltmarshes worldwide. To understand the effects of smooth cordgrass invasion on the habitat use and selection by breeding saltmarsh birds, we compared species number and abundance of breeding birds in native reed (Phragmites australis) and smooth cordgrassinvaded habitats (reed-cordgrass mixed habitats and cordgrass monocultures) at Chongming Dongtan in the Yangtze River estuary, China. We further examined the similarity of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 54 publications
(75 reference statements)
1
38
0
1
Order By: Relevance
“…In contrast, a generalist species like Sylvia atricapilla were not affected by the invasive plant. This pattern corresponds to the findings of a study from China which compared bird responses to the invasion of exotic grass Spartina alterniflora Loisel among species differing in the level of habitat specialization in Yantze River estuary (Ma et al 2011). Here the generalist species did not show any effect of the exotic plant invasion but the specialists were adversely affected.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, a generalist species like Sylvia atricapilla were not affected by the invasive plant. This pattern corresponds to the findings of a study from China which compared bird responses to the invasion of exotic grass Spartina alterniflora Loisel among species differing in the level of habitat specialization in Yantze River estuary (Ma et al 2011). Here the generalist species did not show any effect of the exotic plant invasion but the specialists were adversely affected.…”
Section: Discussionsupporting
confidence: 86%
“…8). Previous studies indicated that the mudflat and shallow water habitat might be replaced by the Scirpus habitat because of the natural succession of the vegetation community (Zhao et al 2009); however, these two types of habitats were drastically replaced by the invasive Spartina habitat in the past decades (Gan et al , 2010Ma et al 2011;Zhao et al 2009). Thus, the negative correlation between the waterbird populations (species number and density) and the mudflat and shallow water habitat might not infer the negative effect of such habitat to waterbirds.…”
Section: Discussionmentioning
confidence: 99%
“…6) and became one of the most dominant plants. As an invasive plant, Spartina habitats, characterized by tall and dense vegetation and reduced diversity and abundance of food resources, are difficult for waterbirds' foraging (Guntenspergen and Nordby 2006;Gan et al 2009Gan et al , 2010Ma et al 2011). In its native range (e.g., northeastern North America), however, Spartina habitats are suboptimal for foraging waterbirds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations